Calculation of the Expanded Uncertainty of the Measurements of the Moisture Content of a Lot of Paper Samples - Chryssou, Katerina; Stassinopoulou, Maria; Lampi, Eugenia (Challenges and Advances in Chemical Science Vol. 8, 2022)
Oven drying at 105oC was considered as a method for the laboratory determination of the dry matter content. It was in this work applicable for papers and boards which do not contain other chemical substances, other than water, in order to determine its moisture content. The moisture content of a paper sample is primarily dependent on the moisture of its surrounding atmosphere. This work was aimed to further apply the ISO approach into the laboratory using four paper substrates and to statistically analyze the results of the experiments. Importance was given as to the appropriate sampling procedure, as well as the conditioning of the quality control sample paper. The determinations of the moisture content were carried out in an oven at 105oC, for 16 hours. The analytical results showed a moisture content of 4%-6%w/w for the paper substrates examined. The moisture content was finally expressed as a percentage mass fraction, according to equation: WH2O=(\({(mo - m1) \over mo}\)) X 100 (1a) where, m0 was the mass of the test piece, before oven drying, or at the time of sampling, in grams, m1 was the mass of the test piece, inside the glass container, after drying to constant mass, in grams. The definition of the standard enthalpy change for the physical transformation of water into vapor, was applied. Also, the combined standard uncertainty was expressed and calculated as: RSDTOTAL=\({\sqrt{RSD_{rMETHOD}2 +({u(wH2O) \over wH2O})^2}}\) (1b) The RSDrMETHOD (repeatability coefficient of variation) was also calculated as CV=sr x100/mean (1c), whereas sr=repeatability standard deviation. The expanded uncertainty, for each of the four different samples of paper, was calculated, for 95% confidence level, and coefficient k=2 according to equation: Uexpanded = 2.RSDTOTAL(1d). The statistical analysis of the gravimetric method described was necessary in order to further develop the analytical method used in the laboratory, and thus provide precise results, as well as calculate the expanded uncertainties, and consequently estimate the expectations of the moisture contents. The study aimed as to determine the uncertainty of the measurement of the moisture content of paper samples in the laboratory and to study the statistics of this measurement in depth, using mathematical models.